Green synthesis of iron hexacyanoferrate nanoparticles: Potential candidate for the degradation of toxic PAHs. Issue 4 (August 2017) - Shanker, Uma; Jassal, Vidhisha; Rani, Manviri
Graphical abstract: Highlights: Quick, green method for synthesis of FeHCF nanostructures utilizing sapindus mukorossi . FeHCF nanoparticles as potential adsorbent cum photocatalyst: sunlight > UV light > dark. Adsorption was found dependent of size and molecular weight of PAHs. Higher degradation of PAHs in water than in the soil is attributed to high efficiency of FeHCFs. The finding of small and non toxic byproducts indicates the positive aspects of process. Abstract: The green synthesis of nanomaterials has gained great attention in the recent times. These methods are not only ecofriendly but also efficient and safer. Iron hexacyanoferrates (FeHCF) are widely used in various applications because of several properties such as ion-exchanging, photomagnetic, electrochromic etc . Hence, their large-scale-synthesis via green routes is the need of present time. Herein we have reported green synthesis of using sapindus-mukorossi as natural surfactant and water as solvent. TEM analysis revealed the formation of FeHCFs nanoparticles (size range:10–60 nm) of hexagonal, rod and spherical shape. Finally, the potential of synthesized FeHCF nanoparticles were investigated for photo-catalytic degradation of hazardous PAHs (anthracene, phenanthrene, chrysene, fluorene, and benzo (a) pyrene) in water as well as soil. Under optimized conditions (PAHs: 50 mg L −1, catalyst dose: 25 mg, neutral pH and solar irradiation), almost all treated PAHs were transformed to smaller non-toxic byproducts. The formation of small and non-toxic metabolites has been confirmed by GC–MS analysis. Anthracene and its isomer named phenanthrene, were degraded to maximum extent of 80 to 90% in both water and soil whereas, the degradation of fluorene, chrysene and benzo ( a ) pyrene were ∼70-80%. Overall, FeHCFs nanoparticles found as excellent adsorbents and photocatalysts for the degradation of persistent organic pollutants. The advantage of present work lies in its quick approach for green synthesis of low-cost and efficient catalyst along with ability to fabricate almost uniformly distributed nanoparticles and their application in making our environment green.